Pengaruh Current Ratio (CR), Total Assets Turnover (TATO) dan Net Profit Margin (NPM) Terhadap Return On Equity (ROE) Pada Perusahaan Telekomunikasi Yang Terdaftar di BEI Periode 2020-2023. - Defia Oktaviana Nengtias; Amanda Oktaviani, Amanda Oktaviani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Abstrak. ROE is a ratio that measures the company's ability to measure net profit after tax with its own capital. While CR is used to measure the company's ability to meet its short-term obligations by using current assets/liquidity, TATO is used to measure the company's efficiency in utilizing its assets to generate income and NPM is used to assess the company's ability to generate profits. This research method uses multiple linear regression analysis method, which allows researchers to see the relationship between two independent variables (CR, TATO and NPM) on the dependent variable (ROE) this study uses a quantitative approach. The data source used in this study is a secondary data source sourced from the financial statements on the Indonesia Stock Exchange (IDX) such as the Balance Sheet and Income Statement. The results of the study indicate that NPM has a very large influence on the dependent variable, namely ROE, while CR, TATO and NPM have no effect.